The International Vitreomacular Traction Study Group classification of vitreomacular adhesion, traction, and macular hole - Duker, Jay S; Kaiser, Peter K; Binder, Susanne; de Smet, Marc D; Gaudric, Alain; Reichel, Elias; Sadda, SriniVas R; Sebag, Jerry; Spaide, Richard F; Stalmans, Peter (Ophthalmology (Rochester, Minn.), 2013)
The International Vitreomacular Traction Study (IVTS) Group was convened to develop an optical coherence tomography (OCT)-based anatomic classification system for diseases of the vitreomacular interface (VMI). The IVTS applied their clinical experience, after reviewing the relevant literature, to support the development of a strictly anatomic OCT-based classification system. A panel of vitreoretinal disease experts was the foundation of the International Classification System. Before the meeting, panel participants were asked to review 11 articles and to complete 3 questionnaires. The articles were preselected based on searches for comprehensive reviews covering diseases of the VMI. Responses to questionnaires and the group's opinions on definitions specified in the literature were used to guide the discussion. Optical coherence tomography-based anatomic definitions and classification of vitreomacular adhesion, vitreomacular traction (VMT), and macular hole. Vitreomacular adhesion is defined as perifoveal vitreous separation with remaining vitreomacular attachment and unperturbed foveal morphologic features. It is an OCT finding that is almost always the result of normal vitreous aging, which may lead to pathologic conditions. Vitreomacular traction is characterized by anomalous posterior vitreous detachment accompanied by anatomic distortion of the fovea, which may include pseudocysts, macular schisis, cystoid macular edema, and subretinal fluid. Vitreomacular traction can be subclassified by the diameter of vitreous attachment to the macular surface as measured by OCT, with attachment of 1500 μm or less defined as focal and attachment of more than 1500 μm as broad. When associated with other macular disease, VMT is classified as concurrent. Full-thickness macular hole (FTMH) is defined as a foveal lesion with interruption of all retinal layers from the internal limiting membrane to the retinal pigment epithelium. Full-thickness macular hole is primary if caused by vitreous traction or secondary if directly the result of pathologic characteristics other than VMT. Full-thickness macular hole is subclassified by size of the hole as determined by OCT and the presence or absence of VMT. This classification system will support systematic diagnosis and management by creating a clinically applicable system that is predictive of therapeutic outcomes and is useful for the execution and analysis of clinical studies.